2012
DOI: 10.1590/s0103-50532012005000008
|View full text |Cite
|
Sign up to set email alerts
|

Currently used pesticides in water matrices in Central-Western Brazil

Abstract: Este estudo fornece dados sobre a presença dos pesticidas atrazina, clorpirifós, a-endossulfam, β-endossulfam, flutriafol, malatiom e metolacloro em água de áreas urbanas e rurais das cidades de Campo Verde e Lucas do Rio Verde, no estado do Mato Grosso, Brasil. Amostras de água superficial, de chuva e subterrânea foram coletadas nas estações de seca e chuva em 2007 e 2008 nessas importantes áreas produtoras de grãos. Os resultados revelaram maior diversidade de substâncias e frequência de detecção em amostras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 33 publications
(46 reference statements)
1
38
0
12
Order By: Relevance
“…Figure 7 shows that concentrations increased from January to March, which are the months with more intensive pesticide application. Our results corroborate the ones found by Lourencetti et al 43 who, similarly, detected β-endosulfan, endosulfan sulfate, metolachlor, Some of these pesticides were also detected by Quaghebeur et al 44 who initiated a pesticide monitoring study in rainwater in Flandres, Belgium. The authors observed that the most frequently detected ones were α, β-endosulfan and endosulfan sulfate, atrazine, diuron, glyphosate and isoproturon from 1997 to 1999.…”
Section: Pesticides In Rainwatersupporting
confidence: 92%
“…Figure 7 shows that concentrations increased from January to March, which are the months with more intensive pesticide application. Our results corroborate the ones found by Lourencetti et al 43 who, similarly, detected β-endosulfan, endosulfan sulfate, metolachlor, Some of these pesticides were also detected by Quaghebeur et al 44 who initiated a pesticide monitoring study in rainwater in Flandres, Belgium. The authors observed that the most frequently detected ones were α, β-endosulfan and endosulfan sulfate, atrazine, diuron, glyphosate and isoproturon from 1997 to 1999.…”
Section: Pesticides In Rainwatersupporting
confidence: 92%
“…após a aplicação que, provavelmente, foi causada por sua rápida volatilização em virtude das altas temperaturas da região. A presença de resíduos de agrotóxicos em amostras de água da chuva tem sido utilizada para demonstrar a volatilização desses compostos em países de clima temperado (Dubus et al, 2000;Vogel et al, 2008;Gish et al, 2011) e tropical (Laabs et al, 2002;Nogueira et al, 2012), inclusive com relatos da presença do endossulfam (Scheyer et al, 2005;Nogueira et al, 2012). Kennedy et al (2001) observaram volatilização de 70% do endossulfam após sua aplicação na cultura do algodoeiro, na Austrália.…”
Section: Methodsunclassified
“…Nos primeiros 41 dias após a aplicação o endossulfam se concentrava na camada superficial do solo e a temperatura média máxima do ar observada neste período foi de 32 °C com precipitação total igual a 233 mm. Estudos têm mostrado evidências de volatilização intensa de agrotóxicos em condições tropicais brasileiras (Laabs et al, 2000;Nogueira et al, 2012;Scorza Júnior & Regitano, 2012). Laabs et al (2000) observaram TD 50 para α-endossulfam igual a 2,5 dias após sua aplicação em condições de campo em Mato Grosso.…”
Section: Methodsunclassified
“…Os estudos realizados em amostras de águas subterrâneas estão concentrados no Estado do Mato Grosso, [56][57][58][59][60]73 . A atrazina e o aloclor foram os pesticidas mais frequentemente dectados dentre os 27 que foram monitoramento nas águas subterrâneas da Slovenia de acordo com Gotvajn e colaboradores.…”
Section: Matriz: áGua Subterrâneaunclassified